ANALISIS MOTIVASI KEAGAMAAN PELAKU BOM BUNUH DIRI (SUICIDE TERRORISM) DI INDONESIA - Raya Elvaretta Maulana; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Suicide bombing is one of the deadliest and most frightening forms of terrorism because the impact caused causes huge losses in the number of casualties and also many aspects of people's lives. The problem is that suicide bombers often act in the name of religion and use their religious views as motivation for their actions. The suicide bombers give meaning to the religious symbols they encounter and then interpret the form of the symbol, namely religious commands such as jihad and also represent symbols that are interpreted as infidels in the wrong way, so this article tries to analyze how important symbols are in the formation of meaning and human behavior. This article uses the symbolic interactionism theory approach in its analysis, by looking for sources from various literatures, namely journals, books, and existing research. and uses a qualitative approach because the data produced is in the form of words or descriptions. Suicide bombers are included in demographic studies because they are part of the human population that can be analyzed statistically.